Role of Phospholipases A2 in Vascular Relaxation and Sympatholytic Effects of Five Australian Brown Snake, Pseudonaja spp., Venoms in Rat Isolated Tissues - Nhi Thuc Vuong; Timothy N. W. Jackson; Christine E. Wright (Frontiers Media S.A., 2021)
Human envenoming by Australian brown snakes (Pseudonaja spp.) may result in potentially life-threatening hypotension and subsequent cardiovascular collapse. There have been relatively few studies of the cardiovascular and sympathetic effects of Pseudonaja spp. venoms. In this study, we have examined the effects of venom from five brown snake species-P. affinis, aspidorhyncha, inframacula, nuchalis, and textilis-on cardiac inotropic and chronotropic responses, vascular tone, and sympathetic nerve-induced vascular contractions in rat isolated tissues. The role of phospholipases A2 (PLA2s) in venom-induced effects was assessed with the sPLA2 inhibitor varespladib. In rat isolated left and right atria, there were no physiologically relevant effects of Pseudonaja venoms (0.1-30 µg/ml) on left atrial force of contraction (inotropy) or right atrial rate (chronotropy). In contrast, in isolated small mesenteric arteries precontracted with a thromboxane mimetic, each of the five brown snake venoms (at 30 µg/ml) caused marked vasorelaxation (−60 to -90% of contractile tone). Pretreatment with varespladib (1 µM) significantly inhibited the vasorelaxation caused by P. aspidorhyncha, P. nuchalis, and P. textilis venoms. Electrically induced sympathetic nerve-mediated contractions of mesenteric arteries were significantly attenuated by only P. textilis, and P. affinis venoms (30 µg/ml) and these sympatholytic effects were inhibited by varespladib (1 µM). Based on their inhibition with the sPLA2 inhibitor varespladib, we conclude that PLA2 toxins in P. aspidorhyncha, P. nuchalis, and P. textilis venoms are involved in brown snake venom-induced vasorelaxation and the sympatholytic effects of P. affinis, and P. textilis venoms. Our study supports the promising potential role of varespladib as an initial (pre-referral) and/or adjunct (in combination with antivenom) therapeutic agent for brown snake envenoming.